Integration of Islamic Social Finance for Sustainable Economic Development in the Rural Areas of Situbondo Regency, East Java, Indonesia - Fauzan Fauzan; Ismail Al Farooqi; Ana Pratiwi; Nur Ika Mauliyah (Journal of Islamic Economics Perspectives, 2025)
Islamic social finance, which includes zakat, infaq, sedekah, and wakaf (ZISWAF), has significant potential to support sustainable economic development in rural areas. This article aims to explore how the integration of Islamic social finance can contribute to the economic empowerment of communities in the rural areas of Situbondo Regency, East Java, Indonesia. Through a qualitative approach, this research analyzes the implementation of Islamic social finance programs and their impact on the economic well-being of the community. The findings indicate that with the synergy between local government, zakat management institutions, and pesantren, Islamic social finance can be an effective instrument in driving economic growth, reducing poverty, and creating sustainable development. This article provides practical recommendations to optimize the potential of Islamic social finance in rural areas.